Risk for lung-related diseases associated with welding fumes in an occupational population: Evidence from a Cox model - Li, Guangming; Jiang, Jinfeng; Liao, Yonggang; Wan, Siyu; Yao, Yong; Luo, Yongbin; Chen, Xuyu; Qian, Huiling; Dai, Xiayun; Yin, Wenjun; Min, Zhiteng; Yi, Guilin; et al. (Frontiers in Public Health, 2022)
Background: Welding fumes are a risk factor for welder pneumoconiosis. However, there is a lack of population information on the occurrence of welding fume-induced lung cancer, and little is known about the welding fume pathogenesis. Methods: Welding fume and metal ion concentrations were assessed in a vehicle factory in Wuhan. A Cox regression model estimated lung-related disease risk in workers by independent and combined factors. Results: Workers’ exposures were divided into four grades; the highest exposure was among the welders in the maintenance workshop, the highest Mn and Fe exposure was 4 grades, and the highest Cr exposure was 3 grades. Subgroup analysis found that the risk of lung-related disease was 2.17 (95% CI: 1.31 to 3.57, p < 0.05) in welders compared with nonwelders, and the risk of pulmonary disease in male welders was 2.24 (95% CI: 1.34 to 3.73, p < 0.05) compared to nonwelders. Smoking welders had a 2.44 (95% CI: 1.32 to 4.51, p < 0.01) higher incidence of lung-related diseases than nonwelders. Total years of work as an independent protective factor for lung-related disease risk was 0.72 (95% CI: 0.66 to 0.78, p < 0.01). As an independent risk factor, high-high and high-low exposure had a 5.39 (95% CI: 2.52 to 11.52, p < 0.001) and 2.17 (95% CI: 1.07 to 4.41, p < 0.05) higher risk for lung-related diseases, respectively. Conclusions: High welding fume exposure is a significant risk factor for lung-related disease in workers.